Paternal low-dose benzo(a)pyrene exposure in rats impairs sexual development and fertility of the paternal lineage in F2 generation: A transgenerational study - Jorge, Bárbara Campos [UNESP]; Stein, Julia [UNESP]; Reis, Ana Carolina Casali [UNESP]; Bueno, Jéssica Nogueira [UNESP]; Paschoalini, Beatriz Rizzo [UNESP]; Moreira, Suyane da Silva [UNESP]; Manoel, Beatriz de Matos [UNESP]; Arena, Arielle Cristina [UNESP] (Elsevier, 2023)
The field of Paternal Origins of Health and Disease (POHaD) is highly relevant but remains under-explored. The F2 generation from males indirectly exposed (F1 - via germ cells) to benzo(a)pyrene (BaP), named PF2, was investigated in this study under parameters of sexual development and reproductive performance of male and female rats. Male Wistar rats (F0) were exposed to BaP (0.1 µg/kg/day) for 31 consecutive days (gavage) during prepuberty. The F0 rats were mated with untreated females to produce male offspring (F1), which were exposed to BaP via germ cells. The F1 males were later mated with untreated females to obtain the PF2 generation, which was the focus of our investigation. Our findings showed that PF2 males exhibited a decrease in anogenital distance, fertility potential, testosterone levels, and type A sperm. Meanwhile, PF2 females had an earlier vaginal opening, lower lordosis scores, and decreased fertility. Furthermore, changes in the histomorphology of the testis/epididymis and ovary/uterus were observed. The repercussions of the PF2 generation indicate that these animals showed losses in both sexual development and fertility potential, and we can conclude that this damage remained due to paternal transgenerational inheritance caused by a low dose of BaP.
Keywords: Endocrine disrupting; Paternal origins of health and disease; Reproductive toxicity; Transgenerational inheritance